Synthesis And Structural Characterization of the PR3-XEUXBA5CU8O18 System (2020)
This research describes the synthesis and characterization of the Pr3-XEuXBa5Cu8O18-δ system with modification levels (x = 0, 0.5, 1, 1.5, 2 and 2.5). The synthesis process was achieved by solid state reaction (SSR). Precursor oxides of Pr6O11, Eu2O3, BaO and CuO were used with purities up to 99.999%. Calcination temperatures were handled at 850 ° C, sintering at 900 ° C and oxygenation at 910 ° C. The structural characterization was determined by X-ray diffraction (XRD). A structural analysis was carried out with Rietveld refinement, where the coexistence of two phases TR358 and TR123 was evidenced. The net parameters were obtained and a perovskite-orthorhombic crystal structure with spatial group Pmmm (47) was achieved. It was concluded that the increase of the X modification level with Eu in the Pr3-XEuXBa5Cu8O18-d system has a large impact on the percentage composition of the phases and structural parameters. The increase or decrease of the value of the net parameters in structure 358 and 123 is affected by the mixture of oxidation states of Pr with those of Eu, causing the cell size to change.